Bioetica clinica - Ethical problems in occupational diagnosis - Magnavita, Nicola; Sacco, Angelo; De Lorenzo, Giuseppe (Medicina e Morale, 1996)
The etiological diagnosis of professional disease is particularly important since it not only makes it possible to adopt suitable preventative, therapeutic and insurance measures for the patient, but it also makes it possible to improve the work environment, which can be appreciated by the whole working community. In order to organize the costs/benefits relationship correctly, the diagnostic checks have to be planned carefully. During the screening phase it is important to provide the workers with the same information and confidentiality as for a general diagnosis. In the more complex etiological diagnostics of professional diseases, the decision regarding the type of examinations to be performed and regarding further examinations has to be made case by case. The condition of each patient and the advantages of these examinations should be taken into consideration, according to a personalistic point of view. Ethical considerations, related to the respect for the patient, will lead to differentiated diagnostics in apparently similar cases. Two clinical cases are described in order to illustrate this possibility.